2016
DOI: 10.3109/13625187.2016.1154144
|View full text |Cite
|
Sign up to set email alerts
|

Women’s preferences for menstrual bleeding frequency: results of the Inconvenience Due to Women’s Monthly Bleeding (ISY) survey

Abstract: The majority of women would prefer to have menstrual periods less than once a month, with a frequency ranging from once every 3 months to no periods at all. This can be explained by the desire to avoid the unpleasant aspects of menstruation and its negative impact on private and professional life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
5
9
0
Order By: Relevance
“…Among the most frequent experiences or symptoms related with menstruation, we identified dysmenorrhea, bloating, irritability, and fatigue; these results are coherent with former studies [10,34,35]. Multiple previous studies already identified dysmenorrhea as being one of the most common menstrual problems among teenagers and young women, worldwide [36][37][38] and, more specifically, among Spanish university students [3].…”
Section: Discussionsupporting
confidence: 89%
“…Among the most frequent experiences or symptoms related with menstruation, we identified dysmenorrhea, bloating, irritability, and fatigue; these results are coherent with former studies [10,34,35]. Multiple previous studies already identified dysmenorrhea as being one of the most common menstrual problems among teenagers and young women, worldwide [36][37][38] and, more specifically, among Spanish university students [3].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings reinforce the evidence that extended-regimen 91-day cycle COC use with low-dose EE during the traditional HFI, with quarterly scheduled bleeding, is a contraceptive option that helps to meet an important treatment need among the growing number of women who desire fewer scheduled bleeding episodes 7,8. Effectiveness of extended-regimen 84/7 COC as a contraceptive method in the real world has been shown through significantly lower unintended pregnancy rates compared with 21/7 or 24/4 regimens, using an insurance claims database 25.…”
Section: Discussionsupporting
confidence: 79%
“…The bleeding patterns reported by women using this extended regimen in our post hoc analysis align well with the preference being expressed by many women for reduced bleeding episodes and increased acceptance of contraceptive-induced amenorrhea 8,11. The replacement of the traditional HFI with continuous low-dose EE in this regimen may further improve hormone withdrawal symptoms experienced by some women18 and may improve cycle control, including unscheduled bleeding/spotting.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations